The unbearable lightness of being - Kundera, Milan; Heim, Michael Henry (New York : Harperperennial, 2009)
Interweaves story and dream, past and present, and philosophy and poetry in a sardonic and erotic tale of two couples--Tomas and Teresa, and Sabina and her Swiss lover, Gerhart.
Keywords: Surgeons -- Czechoslovakia -- Fiction; Man-woman relationships -- Czechoslovakia -- Fiction